Therapeutic monitoring of thiopurine metabolites : validation of an HPLC method and preliminary findings from a small cohort of Malaysian patients with inflammatory bowel disease - Lim, Sheng Zhang; Raja Affendi Raja Ali,; Suzana Makpol,; Chua, Eng Wee (Penerbit Universiti Kebangsaan Malaysia, 2022)
Thiopurine therapy of inflammatory bowel disease (IBD) is guided by the relative blood concentrations 6-thioguanine nucleotides (6-TGN) and 6-methylmercaptopurine (6-MMP). However, their action is altered by in vivo phosphorylation, and this is not normally measured in clinical studies. Hence, we trialled a novel method for profiling phosphorylated thiopurine metabolites and revisited the association between thiopurine metabolites and IBD treatment outcomes. We first optimised and validated a published high-performance liquid chromatography (HPLC) method for measuring the blood levels of thioguanosine monophosphate (TGMP), thioguanosine diphosphate (TGDP), thioguanosine triphosphate (TGTP), and methylthioinosine monophosphate (MeTIMP). Then, we assembled a small cohort of IBD patients (n = 20), who had been treated with azathioprine for at least three months, and obtained blood samples for analysis of the metabolites. The patients received treatments at the Universiti Kebangsaan Malaysia Specialist Centre between March 2018 and April 2019. They were classified as responders (n = 12) or non-responders (n = 6) to azathioprine based on their disease activity scores (CDAI or Mayo score). The HPLC method was precise with intraday and interday variation < 15% for all the tested metabolites, and the relative accuracy ranged from 40.2 to 114.0%. We noted that the responders had higher median 6-TGN but lower median TGTP levels than the non-responders. However, the differences were not statistically significant (Wilcoxon rank-sum tests; 6-TGN, p = 0.925; TGTP, p = 0.189). The higher median 6-TGN level detected in the responders is in keeping with the findings of prior studies, suggesting that HPLC analysis of phosphorylated thiopurine metabolites is both technically feasible and clinically useful.